Mechanical state diagnosis and prefracture of welded joints under fatiguing on the basis of mesoscale criteria - Kibitkin V. V.; Pleshanov V. S.; Lebedeva N. A.; Panin V. E. Viktor Evgenyevich (2004, 2004)
The possibility to evaluate the mechanical state of weldments, their remaining life and prefracture stage diagnostics under multi-cyclic fatiguing on the basis of measurement and analysis of the displacement vector fields by TV-optical method is shown. Measurement conditions of the displacement fields in the vicinity of the crack tip and field evolution under cyclic tension are described. The fatigue failure accumulation criteria that these characterize at the mesoscale level are given